The Effect of Using Interactive Multimedia Design with the STEM VR Approach to Strengthening Pancasila Student Profiles in Elementary School - Buchori, Achmad; ., Sumarno; Septia Devega, Lidya (KnE Social Sciences, 2024)
In producing interactive multimedia, based on STEM VR, with the help of virtual reality which elementary school students need in studying human digestion material, it is hoped that virtual packaging of human digestion material will increase students’ understanding of the topic that cannot be seen by the naked eye. Critical and creative research was carried out on the development of interactive multimedia based on virtual reality for learning about human digestion in fifth-grade elementary schools. This research uses the MDLC stage model with six stages, namely concept, design, material collection, assembly, testing, and distribution. The subject is fifth-grade elementary school. The VR-based interactive multimedia product was validated by experts and continued with a posttest and user response questionnaire with the following results. The science material interactive multimedia product has been validated by material and media experts with results that are very suitable for use in the learning process. Then the product was tested on a limited basis at the SDN Rejosari 01 Semarang school with the influence of 84.4% of students really liking VR-based interactive multimedia products and 15.6% being influenced. Other factors that prevent students from achieving optimal learning outcomes include the school’s lack of VR-related infrastructure so that students are not optimal. Keywords: the effect, interactive multimedia, STEM VR, Science material, elementary school